Active control of flow through the nozzles at sonic Mach number - Ashfaq, Syed; Khan, Sher Afghan; Rathakrishnan, Ethirajan (RS Publication, 2013)
The effectiveness of micro jets to control the base pressure in suddenly expanded axi-symmetric ducts are studied experimentally. As an active control in the form of four micro jets of 1 mm orifice diameter located at 900 intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region was employed. The Mach number of the present study is unity. The area ratio (ratio of area of suddenly expanded duct to nozzle exit area) studied are 2.56, 3.24, 4.84 and 6.25. The L/D ratio of the sudden expansion duct varies from 10 to 1. From the experimental results, it is found that the micro jets can serve as active controllers for base pressure. Further, the control effectiveness of the micro jets is getting enhanced under the influence of favourable pressure gradient. To study the effect of micro jets on the quality of flow in the enlarged duct wall pressure was measured and it is found that the micro jets do not disturb the flow field.